КОМП’ЮТЕРНЕ МОДЕЛЮВАННЯ ТА ДОСЛІДЖЕННЯ ЕНЕРГОЕФЕКТИВНОСТІ ПРОЦЕСІВ ЗАРЯДЖАННЯ АКУМУЛЯТОРНОЇ БАТАРЕЇ ЕЛЕКТРОМОБІЛЯ ВІД БЕЗДРОТОВОГО ЗАРЯДНОГО ПРИСТРОЮ - Жаркін, А.Ф.; Подольцев, О.Д.; Павлов, В.Б. (Інститут електродинаміки НАН України, Київ, 2023)
In the paper, based on the method of computer simulation, the process of charging a lithium-ion battery for an electric car from a wireless charger of the inductive-resonance type was investigated. It is shown that when modeling this process, it is necessary to take into account the simultaneous flow of two processes of different scales in time and interconnected - a short-term high-frequency process in the inverter of the charger with a characteristic time of 10-5 s and a long-term process of charging the battery with a characteristic time of 104 s. Direct numerical calculation of these two processes simultaneously requires significant computer resources. To solve this problem, a new approach is proposed and implemented in the Matlab/Simulink package, according to which, at the first stage, when calculating high-frequency processes in the inverter, there are modified Thevenin and Norton equivalents for a wireless charging device, taking into account the total internal losses in this device, and at in the second stage, the long-term battery charging process is calculated first in the mode of a constant current source, using the constructed Norton equivalent, and then in the mode of a constant voltage source, using the constructed Thevenin equivalent. This approach makes it possible to take into account interrelated and time-varying processes in the inverter and in the battery and to investigate the efficiency of wireless transmission of electrical energy from a stationary power source to a battery located on board an electric vehicle. According to the results of the calculations, it is shown that for the developed device, the integral efficiency of the entire battery charging process when the battery parameter increases from 20% to 95% is 86%. References 9, figures 8.